Problems of influence of marketing research on ownership activity in the sphere grain – growing - Mirzayev, N. S. (Science-based technologies, 2016)
Under the market economy conditions, in the field of grain – grower the most important duty of owners is to provide the increasing and potential need for grain. We can’t forget that we face a lot of problems. In the process we can only find the solution of these problems by investigation of marketing. Marketing investigation is learning the problems purposefully investigating them and applying the system of offers that may provide the solution of their cases. In this article, we investigate the main goal and importance of carrying and marketing researches in the sphere of grain – growing. Moreover, we discuss the problems of the creation of marketing information system of ownership subjects in grain – growing and its influence on production and the sale process. At the same time the influence aspects of marketing on efficient activity of ownership subjects in the direction of development of grain-growing have been investigated. As a result in agricultural and grain market, marketing is of big importance of carrying out of production constantly increasing of product and quality and at the same time solving the problems at times of delivering the product to the consumer, so the main duty of marketing service is carrying out of forming and methods of product selling and expressing the selling place and expressing the service sphere.